A method for treating oil-containing ion exchange resin and its application and regenerated ion exchange resin

By using ammonia aqueous solution and mixed acid solution for multi-step washing in the production process of carbon fiber oil agent, the problem of high water and acid consumption during the washing and regeneration of oleo-containing resins is solved, and efficient resin regeneration and optimized utilization of resources is achieved.

CN115920979BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110947299.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-18
Publication Date
2025-03-04
Estimated Expiration
2041-08-18

AI Technical Summary

Technical Problem

During the production process of carbon fiber oil agent, the washing and regeneration of oil-containing resins requires a large amount of water and hydrochloric acid solution, resulting in waste of water resources and wastewater treatment problems.

Method used

The alkaline washing is performed with aqueous ammonia solution, followed by pickling and neutralization washing with mixed acid solution. Through these steps, the adsorbed carbon fiber oil agent and metal ions in the resin are gradually removed.

Benefits of technology

It significantly reduces water and acid consumption during the washing process, improves the regeneration effect of the resin, reduces the residual amount of carbon fiber oil agent and metal ions, and extends the service life of the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003217184480000071
    Figure BDA0003217184480000071
  • Figure BDA0003217184480000072
    Figure BDA0003217184480000072
  • Figure BDA0003217184480000081
    Figure BDA0003217184480000081
Patent Text Reader

Abstract

The present invention aims to solve the technical problem that the washing and regeneration process of the oil-containing resin in the carbon fiber oil production process requires the consumption of a large amount of water and hydrochloric acid solution, and provides a new method for treating the oil-containing agent ion exchange resin, which uses an ammonia solution and a mixed acid solution to treat the oil-containing resin. The method has the characteristics of low material consumption and good washing and regeneration effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical industry, and specifically relates to a treatment method and application of an oil-containing ion exchange resin and a regenerated ion exchange resin. Background Art

[0002] Carbon fiber oil is mainly composed of modified silicone oil, emulsifier, antistatic agent and other additives. It forms an oil film on the surface of the raw fiber to protect the raw fiber from friction damage and fiber hot melt complications in the pre-oxidation stage. However, ash impurities will inevitably remain in the raw materials and production process of the carbon fiber oil, which will eventually lead to defects in the carbon fiber products and affect product quality. Therefore, it is necessary to strictly control the residual ash content in the carbon fiber oil. Analysis of the ash found that metal elements contributed a considerable proportion.

[0003] In order to remove impurities from carbon fiber oil and reduce ash residue, it is usually necessary to contact the carbon fiber oil with a cation exchange resin to obtain a purified carbon fiber oil after sufficient exchange. However, during the exchange process between the carbon fiber oil and the resin, the resin will absorb a large amount of it to form an oil-containing resin, which will affect the recovery rate of the carbon fiber oil on the one hand, and on the other hand, the carbon fiber oil absorbed by the resin requires a large amount of water and hydrochloric acid solution during the resin washing and regeneration process, and the organic matter content in the wastewater is seriously exceeded (COD is as high as hundreds of thousands of ppm), which affects wastewater treatment, increases environmental pressure, and is also a waste of resources. Summary of the invention

[0004] The present invention aims to solve the technical problem that the washing and regeneration process of the oil-containing resin in the production process of the carbon fiber oil agent needs to consume a large amount of water and hydrochloric acid solution, and provides a new treatment method, which has the characteristics of low material consumption and good washing and regeneration effect.

[0005] One of the purposes of the present invention is to provide a method for treating an oil-containing ion exchange resin, comprising: subjecting the oil-containing ion exchange resin to alkali washing, acid washing and water washing to obtain an ion exchange resin for deoiling, wherein the alkaline solution used in the alkali washing is an ammonia solution, and the acid used in the acid washing is a mixed acid of at least two of acetic acid, phosphoric acid, hydrochloric acid and sulfuric acid.

[0006] The processing method provided by the present invention specifically comprises the following steps:

[0007] Step 1) mixing an oil-containing ion exchange resin with an ammonia solution to obtain a mixture A, and filtering to obtain a filtrate B and a filter cake C;

[0008] Step 2) mixing the filter cake C with the acid solution, heating to obtain a mixture D, and filtering to obtain a filtrate E and a filter cake F;

[0009] Step 3) The filter cake F is mixed with water, heated, and filtered to obtain a filtrate G and a filter cake H. The obtained filter cake H is the ion exchange resin of the degreasing agent.

[0010] In the above treatment method, the oil-containing ion exchange resin is an ion exchange resin containing oil and metal ions.

[0011] Wherein, in the oil-containing ion exchange resin, the oil content is 1-20%, and the metal ion content is 10-1000 ppm, calculated by mass percentage;

[0012] The ion exchange resin is a cation exchange resin;

[0013] The metal ion is selected from K + 、Na + , Ca 2+ Mg 2+ 、Ni 2+ Cr 3+ 、Co 3+ , Mn 2+ , Fe 3+ , Cu 2+ At least one of;

[0014] The oil agent comprises components including blended polyoxyethylene phosphate, fatty alcohol polyoxyethylene ether, octaepoxy hexahedral polysilsesquioxane, and amino-modified silicone oil;

[0015] Wherein, the general formula of polyoxyethylene phosphate is RO-(CH2CH2O) n -PO3H or (RO-(CH2CH2O) n )2-PO3H2; wherein n=1 to 10, and R is an alkyl or aromatic hydrocarbon group having 1 to 10 carbon atoms;

[0016] The general formula of the fatty alcohol polyoxyethylene ether is RO-(CH2CH2O) n -H, wherein n=1 to 10, and R is an alkyl group having 1 to 10 carbon atoms;

[0017] The octa-epoxy hexahedral polysilsesquioxane is selected from at least one of octa-(1,2-epoxy-4-ethylcyclohexyldimethylsilyl) polysilsesquioxane and octa-(3-glycidyloxypropyldimethylsilyl) polysilsesquioxane;

[0018] The amino value of the amino-modified silicone oil is 0.1 to 2;

[0019] Based on 100 parts by weight of the oil in the oil-containing ion exchange resin, the polyoxyethylene phosphate is 20 to 35 parts, the fatty alcohol polyoxyethylene ether is 20 to 35 parts, the octaepoxy hexahedral polysilsesquioxane is 10 to 25 parts, and the amino-modified silicone oil is 25 to 40 parts.

[0020] In step 1) of the above processing method:

[0021] The mass percentage concentration of the ammonia solution is 2 to 20%, preferably 5 to 16%;

[0022] The weight ratio of the oil-containing ion exchange resin to the ammonia solution is 1:(0.2-5), preferably 1:(0.5-3);

[0023] The treatment temperature is 15-30°C, preferably 20-25°C;

[0024] The filter screen size of the filtration is 5 to 50 μm;

[0025] The filtration temperature is 15-30°C, preferably 20-25°C.

[0026] In the present invention, an ammonia solution is first used to wash the oil-containing ion exchange resin, and low-concentration ammonia is used to react with the carbon fiber oil adsorbed in the resin to desorb it, thereby achieving the effect of oil washing and desorption; in addition, when an ammonia solution is used as an alkaline solution for washing, it can be prevented that the metal ions formed hydroxide precipitates by washing with a strong alkaline solution will be prevented, which will block the resin pores, resulting in reduced washing efficiency, and residual impurities in the ion exchange resin after washing.

[0027] In step 2) of the above processing method:

[0028] The acid in the acid solution is at least two of acetic acid, phosphoric acid, hydrochloric acid and sulfuric acid; the hydrogen ion concentration in the acid solution is 0.1 to 3 mol / L, preferably 0.5 to 1.5 mol / L;

[0029] The weight ratio of the filter cake C to the acid solution is 1:(0.1-5), preferably 1:(0.5-2.5);

[0030] The heating temperature is 50-80°C, preferably 55-70°C;

[0031] The heating time is at least 30 minutes, preferably 50 to 100 minutes;

[0032] The filtration temperature is 50-80°C, preferably 55-70°C;

[0033] The filter mesh size of the filtration is 5 to 50 μm.

[0034] The present invention uses a hot acid solution to wash the ion exchange resin after the oil agent is washed and desorbed by an ammonia solution, so as to replace the metal ions, remove the metal ions adsorbed in the ion exchange resin, and neutralize the alkalinity of the solution.

[0035] In step 3) of the above processing method:

[0036] The heating temperature is 30-70°C, preferably 40-55°C;

[0037] The heating time is at least 30 minutes, preferably 50 to 100 minutes;

[0038] The filtration temperature is 30-70°C, preferably 40-55°C;

[0039] The weight ratio of the filter cake F to water is 1:(0.2-3), preferably 1:(0.5-2).

[0040] A second object of the present invention is to provide a regenerated ion exchange resin prepared by the above-mentioned treatment method.

[0041] The third object of the present invention is to provide an application of the treatment method of the oil-containing ion exchange resin described in the above item, including using the treatment method for the regeneration of the oil-containing cation exchange resin in the carbon fiber oil production process.

[0042] In the present invention, an ammonia solution is used to react with the carbon fiber oil adsorbed in the resin to desorb it, and then a mixed acid solution is used for neutralization and washing to remove the adsorbed metal ions, so that the oil and metal ions in the oil-containing cation exchange resin can be removed well. Moreover, the treatment method provided by the present invention uses a specific temperature range to better remove the oil and metal ions. When the treatment temperature is too low or too high, it is affected by the oil component and is not conducive to the removal of the oil or metal ions.

[0043] Compared with the balance method in the prior art, the use of ammonia solution in the present invention can greatly shorten the elution time, accelerate the washing rate and elution effect, not only can remove the oil agent, but also can promote the elution of metal ions, so that the washing and regeneration effect of the oil-containing resin is good, the elution effect of the carbon fiber oil agent and the metal ions in the original oil-containing resin is good, the washing liquid consumption is small, and the service life of the resin is long. DETAILED DESCRIPTION

[0044] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0045] The test method used in the embodiment is as follows:

[0046] Test method for oil content in resin eluent:

[0047] The content of carbon fiber oil in the resin eluent was determined by constant weight method, that is, the proportion of the residual part of the eluent determined by constant weight method at 105°C was the content of carbon fiber oil.

[0048] Test method for carbon fiber oil content in ion exchange resin:

[0049] The balance method is used to determine the content of carbon fiber oil in the resin, that is, the resin is repeatedly washed with pure water 10 times the weight of the resin for 72 hours until constant weight is reached, and then dried at 105°C. The weight of the original oil-containing resin minus the remaining weight of the dried resin is the weight of the carbon fiber oil adsorbed by the resin.

[0050] Metal ion content test:

[0051] ICP (Inductively Coupled Plasma Spectrometer) was used to determine the residual metal ions in the resin and the treated resin.

[0052] The raw materials and sources used in the examples are as follows:

[0053] The cation exchange resin, ammonia water, hydrochloric acid, acetic acid, phosphoric acid, sulfuric acid, etc. used in the examples are all commercially available products.

[0054] The carbon fiber oil raw material used in the embodiment of the present invention has a weight composition of:

[0055] 25 parts polyoxyethylene phosphate (RO-(CH2CH2O) n -PO3H or (RO-(CH2CH2O) n )2-PO3H2; wherein n=6, R is propyl); 30 parts of fatty alcohol polyoxyethylene ether (RO-(CH2CH2O) n -H, wherein n=5, R is ethyl); 15 parts of octa(1,2-epoxy-4-ethylcyclohexyldimethylsilyl)polysilsesquioxane and 30 parts by weight of amino-modified silicone oil (amino value 1.0).

[0056] [Example 1]

[0057] Step 1) 1 kg of oleoresin from the production process of carbon fiber oil is mixed with 1 kg of ammonia solution (concentration 12%) to obtain a mixture A, and stirred at 25° C. for 1 h; the carbon fiber oil content in the oleoresin before treatment is 15.31% by equilibrium method, and the metal ions (including metal ions K) in the oleoresin of the processor are determined by ICP instrument. + 、Na + Mg 2+、Ni 2+ , Fe 3+ , Cu 2+ ) total amount is 417ppm;

[0058] The mixture A was filtered at 25°C with a filter screen size of 45 μm to obtain 1.08 kg of filtrate B and 0.92 kg of filter cake C. The content of carbon fiber oil in filtrate B was determined to be 12.63% by the 105°C equilibrium method. The elution rate of carbon fiber oil in oleoresin was calculated to be 89.11% (elution rate = content of oil in filtrate B / content of oil in oleoresin).

[0059] Step 2) The filter cake C is mixed with 0.92 kg of a mixed acid of hydrochloric acid and acetic acid (wherein the hydrogen ion concentration is 1 mol / L and the molar ratio of hydrochloric acid to acetic acid is 1:1) to obtain a mixture D, and the mixture D is heated to 57° C. for 1 hour; the mixture D is filtered at a constant temperature of 57° C. with a filter screen size of 45 μm to obtain 0.92 kg of filtrate E and 0.92 kg of filter cake F;

[0060] Step 3) The filter cake F was mixed with 0.92 kg of water, heated at 46° C. and filtered with a filter screen size of 45 μm to obtain 0.92 kg of filtrate G and 0.92 kg of filter cake H. The residual amount of carbon fiber oil in the filter cake H was determined by constant weight method to be 0.09%, and the final carbon fiber oil elution rate was 99.43%. The total amount of metal ions in the filter cake H was 23 ppm by ICP instrument, and the metal ion elution rate was 94.92% (metal ion elution rate = (metal ion content in oil-containing resin - metal ion content in final filter cake) / metal ion content in oil-containing resin).

[0061] [Examples 2 to 10]

[0062] The oleoresins in Examples 2 to 10 are the same as those in Example 1, the operating steps are the same as those in Example 1, the specific amounts of compounds used and the operating conditions are shown in Tables 1 and 2, and the elution rates and residual amounts of the obtained oils and metal ions are shown in Table 3.

[0063] Table 1. Raw materials and dosage used in Examples 1 to 10

[0064]

[0065] Table 2. Treatment temperature and filtration temperature in Examples 1 to 10

[0066]

[0067] Table 3. Oil elution rate and residual amount of Examples 1 to 10

[0068]

[0069] [Comparative Example 1]

[0070] The main difference from Example 1 is that the first step of Comparative Example 1 does not use ammonia water, which is as follows:

[0071] Step 1) 1 kg of water and 1 kg of oleoresin are mixed to obtain a mixture A, and the mixture is stirred at 25° C. for 1 h; the carbon fiber oil content in the oleoresin before treatment is 15.31% by equilibrium method, and the metal ions (metal ions including K + 、Na + Mg 2+ 、Ni 2+ , Fe 3+ , Cu 2+ ) total amount is 417ppm;

[0072] The mixture A was filtered at 25°C with a filter screen size of 45 μm to obtain 1.04 kg of filtrate B and 0.96 kg of filter cake C. The content of carbon fiber oil in filtrate B was determined to be 7.04% by the 105°C equilibrium method, and the elution rate of carbon fiber oil in the oil-containing resin was calculated to be 47.83%.

[0073] Step 2) The filter cake C is mixed with 0.96 kg of a mixed acid of hydrochloric acid and acetic acid (wherein the hydrogen ion concentration is 1 mol / L and the molar ratio of hydrochloric acid to acetic acid is 1:1) to obtain a mixture D, and the mixture D is heated to 57° C. for 1 h; the mixture D is filtered at a constant temperature of 57° C. with a filter screen size of 45 μm to obtain 0.97 kg of filtrate E and 0.95 kg of filter cake F;

[0074] Step 3) The filter cake F was mixed with 0.95 kg of water, heated to 46 ° C, the filter size was 45 μm, and filtered to obtain 0.95 kg of filtrate G and 0.95 kg of filter cake H. The residual amount of carbon fiber oil in the filter cake H was determined by constant weight method to be 3.77%, and the final carbon fiber oil elution rate was calculated to be 76.63%. The total amount of metal ions in the filter cake H was determined by ICP instrument to be 83 ppm, and the metal ion elution rate was calculated to be 81.09%.

[0075] Since ammonia water was not used for elution in the first step, the elution rate of the oil agent in the first step decreased, and the residual oil agent affected the elution of metal ions in the subsequent steps.

[0076] [Comparative Example 2]

[0077] The main difference from Example 1 is that in the first step of Comparative Example 2, NaOH solution is used instead of ammonia water, as follows:

[0078] Step 1) 1 kg of oleoresin from the production process of carbon fiber oil was mixed with 1 kg of 12% NaOH solution to obtain a mixture A, which was stirred at 25°C for 1 hour; the carbon fiber oil content in the oleoresin before treatment was 15.31% using a balance method, and the metal ions (metal ions including K + 、Na + Mg 2+ 、Ni 2+ , Fe 3+ , Cu 2+ ) total amount is 417ppm;

[0079] The mixture A was filtered at 25°C with a filter screen size of 45 μm to obtain 1.07 kg of filtrate B and 0.93 kg of filter cake C. The content of carbon fiber oil in filtrate B was determined to be 11.25% by the 105°C equilibrium method, and the elution rate of carbon fiber oil in the oil-containing resin was calculated to be 78.65%.

[0080] Step 2) The filter cake C is mixed with 0.93 kg of a mixed acid of hydrochloric acid and acetic acid (wherein the hydrogen ion concentration is 1 mol / L and the molar ratio of hydrochloric acid to acetic acid is 1:1) to obtain a mixture D, and the mixture D is heated to 57° C. for 1 h; the mixture D is filtered at a constant temperature of 57° C. with a filter screen size of 45 μm to obtain 0.94 kg of filtrate E and 0.92 kg of filter cake F;

[0081] Step 3) The filter cake F was mixed with 0.92 kg of water, heated to 46 ° C, with a filter screen size of 45 μm, and filtered to obtain 0.92 kg of filtrate G and 0.92 kg of filter cake H. The residual amount of carbon fiber oil in the filter cake H was determined by constant weight method to be 1.39%, and the final carbon fiber oil elution rate was calculated to be 91.63%. The total amount of metal ions in the filter cake H was determined by ICP instrument to be 91 ppm, and the metal ion elution rate was calculated to be 79.92%.

[0082] In the first step, NaOH solution is used for elution. The elution rate of the oil agent in the first step decreases, and the residual oil agent affects the elution of metal ions in the subsequent steps.

[0083] [Comparative Example 3]

[0084] The main difference from Example 1 is that the heating temperatures in the third and fourth steps of Comparative Example 3 are relatively high, as follows:

[0085] Step 1) 1 kg of oleoresin from the production process of carbon fiber oil was mixed with 1 kg of ammonia solution (concentration 12%) to obtain a mixture A, and stirred at 25°C for 1 hour; the carbon fiber oil content in the oleoresin before treatment was 15.31% by equilibrium method, and the metal ions (metal ions including K + 、Na+ Mg 2+ 、Ni 2+ , Fe 3+ , Cu 2+ ) total amount is 417ppm;

[0086] The mixture A was filtered at 25°C with a filter screen size of 45 μm to obtain 1.08 kg of filtrate B and 0.92 kg of filter cake C. The content of carbon fiber oil in filtrate B was determined to be 14.05% by the 105°C equilibrium method, and the elution rate of carbon fiber oil in the oil-containing resin was calculated to be 89.11%.

[0087] Step 2) The filter cake C is mixed with 0.92 kg of a mixed acid of hydrochloric acid and acetic acid (wherein the hydrogen ion concentration is 1 mol / L and the molar ratio of hydrochloric acid to acetic acid is 1:1) to obtain a mixture D, and the mixture D is heated to 80° C. for 1 h; the mixture D is filtered at a constant temperature of 80° C. with a filter screen size of 45 μm to obtain 0.92 kg of filtrate E and 0.92 kg of filter cake F;

[0088] Step 3) The filter cake F was mixed with 0.92 kg of water, the filtration temperature was 60 ° C, the filter size was 45 μm, and 0.92 kg of filtrate G and 0.92 kg of filter cake H were obtained by filtration. The residual amount of carbon fiber oil in the filter cake H was determined to be 0.13% by constant weight method, and the final carbon fiber oil elution rate was calculated to be 92.26%. The total amount of metal ions in the filter cake H was determined to be 69 ppm by ICP instrument, and the metal ion elution rate was calculated to be 84.78%.

[0089] Since the elution temperature in the third and fourth steps is relatively high, the final oil elution rate decreases, and the elution rate of metal ions also decreases.

[0090] [Comparative Example 4]

[0091] The main difference from Example 1 is that in the second step of Comparative Example 4, a hydrochloric acid solution of the same concentration is used instead of a mixed acid, as follows:

[0092] Step 1) 1 kg of oleoresin from the production process of carbon fiber oil is mixed with 1 kg of 12% ammonia solution to obtain a mixture A, and stirred at 25°C for 1 hour; the carbon fiber oil content in the oleoresin before treatment is 15.31% by equilibrium method, and the metal ions (metal ions including K + 、Na + Mg 2+ 、Ni 2+ , Fe 3+ , Cu 2+ ) total amount is 417ppm;

[0093] The mixture A was filtered at 25°C with a filter screen size of 45 μm to obtain 1.08 kg of filtrate B and 0.92 kg of filter cake C. The content of carbon fiber oil in filtrate B was determined to be 12.63% by the 105°C equilibrium method, and the elution rate of carbon fiber oil in the oil-containing resin was calculated to be 89.11%.

[0094] Step 2) The filter cake C is mixed with 0.92 kg of hydrochloric acid, wherein the hydrogen ion concentration is 1 mol / L, to obtain a mixture D, and the mixture D is heated to 57° C. for 1 hour; the mixture D is filtered at a constant temperature of 57° C. with a filter screen size of 45 μm to obtain 0.92 kg of filtrate E and 0.92 kg of filter cake F;

[0095] Step 3) The filter cake F was mixed with 0.92 kg of water, heated to 46 ° C, with a filter screen size of 45 μm, and filtered to obtain 0.92 kg of filtrate G and 0.92 kg of filter cake H. The residual amount of carbon fiber oil in the filter cake H was determined by constant weight method to be 1.12%, and the final carbon fiber oil elution rate was 93.26%. The total amount of metal ions in the filter cake H was 112 ppm by ICP instrument, and the metal ion elution rate was 75.3%.

[0096] In Comparative Example 4, hydrochloric acid solution was used for elution in the second step, and both the oil elution rate and the metal ion elution rate decreased.

[0097] The specific method for treating the oil-containing resin in the production process of the carbon fiber oil agent proposed by the present invention has been described through a preferred embodiment. It is obvious that relevant technical personnel can modify or appropriately change and combine the structure and preparation method described herein without departing from the content, spirit and scope of the present invention to implement the technology of the present invention. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A method for treating an oil-containing ion exchange resin, comprising: The oil-containing ion exchange resin is subjected to alkali washing, acid washing and water washing to obtain an ion exchange resin for an oil remover, wherein the oil-containing ion exchange resin is an ion exchange resin containing an oil and metal ions, the alkaline solution used in the alkali washing is an ammonia solution, the acid used in the acid washing is a mixed acid of at least two of acetic acid, phosphoric acid, hydrochloric acid and sulfuric acid, and the hydrogen ion concentration of the acid solution used in the acid washing is 0.1-3 mol / L.

2. The processing method according to claim 1, characterized in that: The processing method specifically comprises the following steps: Step 1) mixing the oil-containing ion exchange resin with an ammonia solution to obtain a mixture A, and filtering to obtain a filtrate B and a filter cake C; Step 2) mixing the filter cake C with the mixed acid solution, heating to obtain a mixture D, and filtering to obtain a filtrate E and a filter cake F; Step 3) The filter cake F is mixed with water, heated, and filtered to obtain a filtrate G and a filter cake H. The obtained filter cake H is the ion exchange resin of the degreasing agent.

3. The processing method according to claim 2, characterized in that: In terms of mass percentage, in the oil-containing ion exchange resin, the oil content is 1-20%, and the metal ion content is 10-1000 ppm.

4. The processing method according to claim 1, characterized in that: The ion exchange resin is a cation exchange resin; and / or, The oil agent comprises components including blended polyoxyethylene phosphate, fatty alcohol polyoxyethylene ether, octaepoxy hexahedral polysilsesquioxane, and amino-modified silicone oil; and / or, The metal ions include K + 、Na + , Ca 2+ Mg 2+ 、Ni 2+ Cr 3+ 、Co 3+ , Mn 2+ , Fe 3+ , Cu 2+ At least one of .

5. The processing method according to claim 4, characterized in that: The general formula of the polyoxyethylene phosphate is RO-(CH2CH2O) n -PO3H or (RO-(CH2CH2O) n )2-PO3H2; wherein n=1-10, R is an alkyl or aromatic hydrocarbon group having 1-10 carbon atoms; and / or, The general formula of the fatty alcohol polyoxyethylene ether is RO-(CH2CH2O) n -H, wherein n=1-10, and R is an alkyl group having 1-10 carbon atoms; and / or, The octa-epoxy hexahedral polysilsesquioxane is selected from at least one of octa-(1,2-epoxy-4-ethylcyclohexyldimethylsilyl) polysilsesquioxane and octa-(3-glycidyloxypropyldimethylsilyl) polysilsesquioxane; and / or, The amino value of the amino-modified silicone oil is 0.1-2.

6. The processing method according to claim 4, characterized in that: Based on 100 parts by weight of the oil in the oil-containing ion exchange resin, the polyoxyethylene phosphate is 20 to 35 parts, the fatty alcohol polyoxyethylene ether is 20 to 35 parts, the octaepoxy hexahedral polysilsesquioxane is 10 to 25 parts, and the amino-modified silicone oil is 25 to 40 parts.

7. The processing method according to claim 2, characterized in that: In the step 1): The mass percentage concentration of the ammonia solution is 2-20%; and / or, The weight ratio of the oil-containing ion exchange resin to the ammonia solution is 1:(0.2-5); and / or, The mixing temperature is 15-30°C; and / or, The filter screen size of the filtration is 5-50 μm; and / or, The filtration temperature is 15-30°C.

8. The processing method according to claim 7, characterized in that: In the step 1): The mass percentage concentration of the ammonia solution is 5-16%; and / or, The weight ratio of the oil-containing ion exchange resin to the ammonia solution is 1:(0.5-3); and / or, The mixing temperature is 20-25°C; and / or, The filtration temperature is 20-25°C.

9. The processing method according to claim 2, characterized in that: In the step 2): The acid in the acid solution is at least two of acetic acid, phosphoric acid, hydrochloric acid and sulfuric acid; and / or, The weight ratio of the filter cake C to the acid solution is 1:(0.1-5); and / or, The heating temperature is 50-80°C; and / or, The heating time is at least 30 minutes; and / or, The filtration temperature is 50-80°C; and / or, The filter mesh size of the filtration is 5-50 μm.

10. The processing method according to claim 9, characterized in that: In the step 2): The hydrogen ion concentration in the acid solution is 0.5-1.5 mol / L; and / or, The weight ratio of the filter cake C to the acid solution is 1:(0.5-2.5); and / or, The heating temperature is 55-70° C.; and / or, The filtration temperature is 55-70°C.

11. The processing method according to claim 2, characterized in that: In the step 3): The heating temperature is 30-70°C; and / or, The heating time is at least 30 minutes; and / or, The filtration temperature is 30-70°C; and / or, The weight ratio of the filter cake F to water is 1:(0.2-3).

12. The processing method according to claim 11, characterized in that: In the step 3): The heating temperature is 40-55°C; and / or, The filtration temperature is 40-55°C; and / or, The weight ratio of the filter cake F to water is 1:(0.5-2).

13. A regenerated ion exchange resin prepared by the treatment method according to any one of claims 1 to 12.

14. An application of the treatment method of an oil-containing ion exchange resin according to any one of claims 1 to 12, comprising using the treatment method for regenerating an oil-containing cation exchange resin in a carbon fiber oil production process.

Citation Information

Patent Citations

  • Load metal ball shaped active carbon material and preparation, use method thereof

    CN101385966A

  • Method for regenerating inactivated strongly acidic cation-exchange resin

    CN103071547A